The sawfly genus Pleroneura (Hymenoptera, Xyelidae) of Japan: P. itoi n. sp. and a key to species - Shinohara, Akihiko (Zootaxa, 2016)
Pleroneura itoi n. sp. is described from a female specimen collected on Mt. Wasamatayama, Nara prefecture, Honshu, Japan, and a key is given for the four species of Pleroneura from Japan. The new species is well characterized by the richly pale-marked head and the small and slender valvula 3.